MENINGKATKAN PERBENDAHARAAN KOSAKATA BAHASA INGGRIS MAHASISWA TUNARUNGU MELALUI MEDIA KARTU KATA (FLASH CARD) - Aswar aswar (Jurnal Penelitian Pendidikan Khusus, 2012)
The background research is the lack of english vocabulary in deaf student majoring in Special Need Education (PLB) FIP UNP Padang. Thus, the author helps to improve English vocabulary that is specific to the noun vocabulary through Flash Cards. This study used a single subject research approach (SSR) with the A-B design and data analysis techniques using visual graphical analysis. The subjects were students with hearing impairment, given the intervention by using the flash cards. From the results of this research results show English vocabulary (noun) an increase controlled subjects. In the analysis between conditions showed a tendency towards a positive (+) change of variable to variable rendt stability, trend and level changes increased from 15% to 90%, and 0% Percentage Overlap of data meaningful research results accepted. Based on the results of data analysis it can be concluded that the Treasury Vocabulary English (Noun) The Deaf Students Can Enhanced Media Flash Card. The authors suggest to students that English vocabulary is lacking, could use a media card in increasing vocabulary words and no exception to teachers who want to apply the word cards to students in improving the vocabulary of the students.